Antibacterial activity of Spondias mombin on superinfecting bacteria in the oral environment (Research, Society and Development, 2020)
Objective: To evaluate in vitro the antimicrobial action of the hydroalcoholic extract of the leaf of Spondias mombin (cajá), on Staphylococcus aureus (ATCC 25923) and Enterococcus faecalis (ATCC 29212). Methodology: The microbial strains were grown in BHI broth (Brain Heart Infusion) and incubated at 37 ° C for 18-20 hours. In petri dishes containing Mueller Hinton Agar, inoculated saline solution was introduced with each microbial growth and five standardized holes of approximately six mm in diameter were made. 50µL of the test substance (Crude Extract - EB / Substance Pure - SP until 1: 512 dilution) was introduced into the holes and incubated at 37 ° C for 24 hours. The assay was performed in duplicate on each strain. Chlorhexidine digluconate 2% and sodium hypochlorite 2.5% were used as positive controls. For data analysis, statistical parameters were used that included values: minimum, maximum, average and standard deviation. Mann-Whitney U nonparametric test was applied to compare the minimum inhibitory concentration of the substances. Results: It was observed that the chlorhexidine and the extract of the caja showed superior performance to the sodium hypochlorite 2.5% on the tested bacteria. According to the results of the Mann Whitney U test, there was a statistically significant difference only between the extract of caja and sodium hypochlorite 2.5% (p